Limited Improvements in Health Behaviors Suggest Need to Review Approaches to Health Promotion: A Repeated, Cross-Sectional Study. Issue 4 (July 2022) - Becker, Craig M.; Sewell, Kerry; Bian, Hui; Lee, Joseph G. L.
Purpose. To broadly assess changes in key health behaviors (physical activity, fruit and vegetable consumption, smoking, and alcohol consumption) and one outcome (body mass index) between 2001-2006 and 2011-2016. Design. Repeated cross-sectional study. Setting. The United States of America. Participants. Noninstitutionalized adults age 24 to 39 participating in the National Health and Nutrition Examination Survey. Analysis. We used 2-sample t tests and χ 2 tests to compare differences in health behaviors between the 2 time periods. Results. Data revealed a downward trend in both moderate and vigorous physical activity (P = .00), and fruit and vegetable consumption decreased (P = .003). Cigarette smoking decreased (P = .04), and there was no substantive change in heavy drinking between the 2 time periods. Body mass index was higher in the later time period (P = .00). Conclusion. Despite sustained funding efforts, we found little evidence that health behaviors improved between the 2 time periods. Indeed, many health behaviors have remained the same or worsened over time. These findings suggest the need to reflect on the appropriateness of the health promotion approaches being used.